Application of brand management as a consideration in enhancing interior design for selected Filipino specialty restaurants - Arcilla, Crisette B.; Faustino, Johanna Acab. (2010.)
The objective of this study was to determine how brand management could be integrated into the design process of a restaurant and physically manifest in its interior to boost the establishment's success and sustainability. The descriptive method was used to determine how the interior design of the selected restaurants could effectively be integrated with brand management. Interviews and surveys were conducted, along with photo documentation and observations of three different Filipino restaurants belonging to one restaurant group. Physical manifestations of brand management were documented and evaluated. Purposive sampling was applied in this study. One restaurant group owner was interviewed and forty-eight respondents between 30-65 years old participated in the survey. The data of this research was presented according to the five main components of brand management - brand essence, values and discriminator, consumer benefits, competition and target market. It was found that design and ambience indirectly contribute to the success of the business because it is able to affect the brand message that the space communicates, the type of market a restaurant draws in and how the dining experience is set apart from competitors. Considerations such as the type of furniture and accessories, color schemes and logo placement affect the brand experience within the restaurant and its ability to make a lasting impression to customers. For future researches, more than one restaurant group is recommended for a more comprehensive comparison of brand management strategies. It is also recommended that additional insights be sourced from the designers of the restaurants.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Interior decoration; Restaurants -- Philippines